2014
DOI: 10.4172/2157-7013.1000164
|View full text |Cite
|
Sign up to set email alerts
|

IFNGamma Priming Protects Fetal and Embryonic MSC from NK Cell-Mediated Killing and Improves their Immunosuppressive Properties: Role of Activating and Inhibitory Receptors

Abstract: The enhancement of Mesenchymal Stem Cells (MSC) immunosuppressing function can favour the engraftment of MSC employed in tissue repair. IFN-γ is a pro-inflammatory cytokine, which induces tolerogenic molecules in bone marrow (BM) MSC. We have investigated the interaction of IFN-γ primed MSC from fetal (FL-MSC) and embryonic (ES-MSC) origin with natural killer (NK) cells. IFN-γ -primed FL-/ES-MSC were less susceptible to NK cell-mediated killing, where a major role was played by the IFN-γ-induced up-regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…However, the researchers showed that MSCs were protected from lysis by NK cells by increasing IFN-γ during inflammatory responses. Spagiari et al [ 57 ] in a study on BM-MSC, and Giuliani et al [ 95 ] in a study on fetal-MSC (FL-MSC) and embryonic-MSC (ES-MSC), investigated the effect of IFN-γ on the protection of MSC against NK cells. They showed that IFN-γ increased HLA class I and HLA-E molecules expression in MSCs and decreased lysis of MSCs by NK cells.…”
Section: Nk Cell Effect On Mscsmentioning
confidence: 99%
“…However, the researchers showed that MSCs were protected from lysis by NK cells by increasing IFN-γ during inflammatory responses. Spagiari et al [ 57 ] in a study on BM-MSC, and Giuliani et al [ 95 ] in a study on fetal-MSC (FL-MSC) and embryonic-MSC (ES-MSC), investigated the effect of IFN-γ on the protection of MSC against NK cells. They showed that IFN-γ increased HLA class I and HLA-E molecules expression in MSCs and decreased lysis of MSCs by NK cells.…”
Section: Nk Cell Effect On Mscsmentioning
confidence: 99%
“…These immune cells are typically activated using antibodies, inflammatory cytokines or lipopolysaccharides, followed by coculture of the immune cells with MSCs, then analysis of immune cell proliferation, function and activity. Priming of MSCs with cytokines such as IFNg and TNFa improves the ability of MSCs to suppress T cell proliferation and activation [209], B cell proliferation [209] and NK cellÀmediated cytotoxicity [214] in co-culture assays. Such techniques involving specific immune cell populations, combined with the appropriate stimulus to both activate immune cells and prime the immunomodulatory capability of MSCs, represent a physiologically relevant assay to characterize the functional potency of MSCs.…”
Section: Potency Assays To Evaluate Msc Immunosuppressive Capabilitymentioning
confidence: 99%